2017
DOI: 10.1159/000458767
|View full text |Cite
|
Sign up to set email alerts
|

Clustered Cardiovascular Risk Factors Are Associated with Inflammatory Markers in Adolescents

Abstract: Background: Clusters of cardiovascular risk (CVR) factors are associated with an increased risk of developing cardiovascular diseases (CVDs). This cross-sectional study assessed the associations between classic CVR factor clusters and inflammatory markers in Brazilian adolescents. Methods: Measurements included anthropometric, clinical and biochemical parameters and selected inflammatory markers in 487 adolescents (236 boys/251 girls; 12.06 ± 1.41 years). Results: After stratifying the population by gender and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…Moreover, we have found significant negative correlation of IL-1β gene expression with HDL cholesterol and a positive correlation with triglycerides in healthy adults. Similar results have been previously observed by Teixeira Sliva et al in young adolescent population [ 34 ]. The negative association between IL-1β and HDL cholesterol concentration found in our healthy control group is not surprising, as HDL cholesterol is known to have anti-inflammatory effects [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we have found significant negative correlation of IL-1β gene expression with HDL cholesterol and a positive correlation with triglycerides in healthy adults. Similar results have been previously observed by Teixeira Sliva et al in young adolescent population [ 34 ]. The negative association between IL-1β and HDL cholesterol concentration found in our healthy control group is not surprising, as HDL cholesterol is known to have anti-inflammatory effects [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have also shown that low-grade systemic inflammation leads to an increased risk of CVD [19][20][21]. The common inflammatory cytokines include interleukin-1β (IL-1β) and interleukin-6 (IL-6) which indicate greater susceptibility to the development of CVD [22][23][24]. Therefore, to investigate the CVDs protection effect of FAHFAs, we explored the correlation of major endogenous FAHFAS with several cardiovascular biomarkers and their anti-inflammatory effects on RAW 264.7 macrophage cells.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on the relationship between inflammation and psychological variables, we found that many reports have studied the association of genetic, environmental, psychological, and personal factors with inflammatory markers [ 3 , 4 , 5 , 6 , 7 , 8 ]. Among the main inflammatory markers studied are the C reactive protein (CRP), inflammatory interleukins IL-1 and IL-6, and tumor necrosis factor alpha (TNF-α) [ 6 , 9 ]. CRP is an inflammatory protein synthetized by Kupffer cells in the liver, in response to acute inflammatory events, and depending on their values, it can be indicative of chronic inflammatory states [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%